Efficacy of a targeted intervention method to improve the use of hearing protection devices among agro-industrial workers in Malaysia - Ammar, Sirri; Daud, Aziah; Ismail, Ahmad Filza; Razali, Ailin (MDPI, 2022)
Hearing-protection devices (HPD) are crucial in protecting workers from hazardous noise exposures. Despite the mandatory implementation of hearing-conservation programmes at the workplace, compliance with proper HPD usage among workers has been shown to be poor. This study aims to develop and determine the efficacy of a targeted intervention to improve the use of HPD among noise-exposed agro-industrial workers. One group of workers was given a targeted training module, while another group received a standard training module. Their self-reported HPD use and the intention to use HPD in the future were compared to evaluate the effect of the interventions. The targeted intervention significantly increased HPD use after four months compared to the control intervention. The findings showed that improving the workers’ compliance with HPD usage is possible by implementing a well-designed training method.